A metal-organic framework-derived Fe–N–C electrocatalyst with highly dispersed Fe–Nx towards oxygen reduction reaction. (18th October 2019) - Zhang, Xiangkun; Huang, Xiaobo; Hu, Wenhui; Huang, Yongmin
Abstract: Metal and nitrogen co-doped catalysts have been promising alternatives to platinum group metal (PGM) catalysts for oxygen reduction reaction (ORR) over the past few decades. Herein, we have synthesized an efficient Fe–N–C catalyst by the co-calcination of NH2 -MIL-101@PDA and melamine. The best Fe–N–C shows a positive half-wave potential of 0.844 V, which is 14 mV higher than that of Pt/C catalyst, as well as superior methanol resistance and long-term durability in alkaline electrolyte. In addition, Fe–N–C also exhibits pronounced catalytic activity and a direct 4e − reaction pathway in acid electrolyte. We ascribed the excellent ORR performance of Fe–N–C to its crumpled structure, large specific surface area (584.6 m 2  g −1 ) and high content of Fe-Nx sites (1.22 at. %). This study provides a simple way for the fabrication of excellent PGM-free ORR catalysts. Graphical abstract: Image 1 Highlights: Efficient catalysts are synthesized through a simple co-calcination process. The best Fe–N–C shows better ORR performance than Pt/C in alkaline electrolyte. Superior ORR performance is ascribed to the high content of Fe-Nx (1.22 at. %) and N (8.07 at. %). PDA and melamine play crucial roles in improving catalytic performance.